The Role of the Constitutional Judiciary in Establishing the Principles of Secession is a Study in the Canadian Supreme Court's Decision regarding the Secession of Quebec. - Abdullah, Khamosh Omer (Journal of Legal and Political Studies, 2019)
The issue of "secession" is one of the most difficult issues that faced the Supreme Court of Canada, after two referendums in 1980 and 1995, and in both of them voters narrowly voted to stay within Canada. On 20th of August 1998, the Supreme Court of Canada issued a judgment on the legality of unilateral secession of Quebec. In its advisory opinion, the Court emphasized "the four basic principles of the Constitution", which are "federalism, democracy, rule of law, respect for minorities" in accordance with the Canadian constitutional law, separation under these principles requires negotiation of the amendment of the Canadian Constitution. The Court considered that the only legal way under which Quebec would be separated from Canada was through the amendment mechanisms of the 1982 Constitutional Law. The Court referred to the obligation to negotiate as a guarantee of the success of the separation. The Court noted that the parties concerned should negotiate a future settlement. In terms of the referendum, the Court noted the need for adequate support from the population of Quebec in favor of separation. The wording of the question should be unambiguous. The ballot in favor of secession must be supported by a "clear majority", without indicating the proportion of that majority. Following the Judgment from the Court on the secession of Quebec, the federal government began to set the conditions laid down by the Court in a so-called "Clarity Law" in a legislative framework. The essence of the Clarity act derives from the advisory opinion (judgment) of the Court. The Law deals with the clarity of the question and the clarity of the majority and the issues to be discussed during the negotiations.
Keywords: secession; Court of Canada; referendums; amendment; federal government